Increasing Post‐Digestive Solubility of Curcumin Is the Most Successful Strategy to Improve its Oral Bioavailability: A Randomized Cross‐Over Trial in Healthy Adults and In Vitro Bioaccessibility Experiments - Flory, Sandra; Sus, Nadine; Haas, Kathrin; Jehle, Sina; Kienhöfer, Eva; Waehler, Reinhard; Adler, Günther; Venturelli, Sascha; Frank, Jan (Molecular nutrition & food research, 2021)
Scope Different mechanistic approaches to improve the low oral bioavailability of curcumin have been developed, but not yet directly compared in humans. Methods and Results In a randomized, double‐blind, cross‐over trial with 12 healthy adults, the 24 h pharmacokinetics of a single dose of 207 mg curcumin is compared from the following formulations: native, liposomes, with turmeric oils, with adjuvants (including piperine), submicron‐particles, phytosomes, γ‐cyclodextrin complexes, and micelles. No free, but only conjugated curcumin is detected in all subjects. Compared to native curcumin, a significant increase in the area under the plasma concentration–time curve is observed for micellar curcumin (57‐fold) and the curcumin‐γ‐cyclodextrin complex (30‐fold) only. In vitro digestive stability, solubility, and micellization efficiency of micellar curcumin (100%, 80%, and 55%) and curcumin‐γ‐cyclodextrin complex (73%, 33%, and 23%) are higher compared to all other formulations (<72%, <8%, and <4%). The transport efficiencies through Caco‐2 cell monolayers of curcumin from the digested mixed‐micellar fractions did not differ significantly. Conclusion The improved oral bioavailability of micellar curcumin, and to a lesser extent of γ‐cyclodextrin curcumin complexes, appears to be facilitated by increased post‐digestive stability and solubility, whereas strategies targeting post‐absorptive processes, including inhibition of biotransformation, appear ineffective. Pharmacokinetics of 207 mg curcumin from seven different formulations with intended improved bioavailability were compared to identical doses of native curcumin in healthy adults. Curcumin incorporated into micelles or γ‐cylcodextrin complexes showed higher bioavailability in vivo and improved solubility and micellization efficiency after in vitro digestion. Curcumin permeability through Caco‐2 cell monolayers is not affected by its formulation.